Establecer un régimen normativo en la ley del seguro social, encaminada al aseguramiento de las amas de casa y toda persona que se encuentre en situación de desempleo. - Coronel Troya, Eyasmin Francisca (2012)
My research work entitled TO ESTABLISH A NORM INSIDE THE SOCIAL SECURITY LAW, FOCUSED ON THE INSURANCE OF HOUSEWIVES AND UNEMPLOYMED PEOPLE" is focused on the social security failures in our country and the consequences that come from those. The social security in the Ecuador is a national system created to protect workers from risks. This is why the Constitution mentions right and duty characteristics for the social security system, based on the constitutional principles of universality, solidarity, obligation, fairness, efficiency, sufficiency, transparency and participation, being the government in charge of these policies. The security refers mainly to a social well-being environment related with social protection or covering of the main social needs as health, poverty, elderliness, disabling problems, unemployment, families with children and others. Something important is that the Constitution guarantees people in unemployment situation and housewives; and this is something new regarding social rights, which makes the state guarantee to these people the access to social security. As Ecuadorian we are also responsible for the social security, as it is expressed in the art. 83 of the Constitution; it mentions that we should cooperate along with the government in the social security matters. The problem itself in our research work deals with the unemployed people and housewives insurance. For an unemployed person to be insured there must be an employer or someone to pay for that insurance, which will not happen if there is no retribution on the part of the unemployed. The same thing happens with housewives without a salary, there must be a correlation among the housewife and the people she serves, but this is very difficult to prove, since the domestic chores are in fact an essential element inside the marriage or free union. To conclude it can be said that there are some legal inaccuracies in the Social Security Law; since this law does not say that housewives or unemployed people should have insurance. Among people under direct protection that this social norm embraces, it does not include housewives and unemployed people. It does not mention anything about people who are devoted to house chores, farmers, and unemployed people, and what is worst; it does not say anything on social help to wives and mothers, that is to say, women who are devoted to be housewives.